2021
DOI: 10.3389/fonc.2021.666145
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Mutation in Non-Tyrosine Kinase Domain of ROS1 as a Potential Predictor of Immune Checkpoint Inhibitors in Melanoma

Abstract: PurposeDespite the success of targeted therapy in c-ros oncogene 1 (ROS1)-rearranged cancers, especially non-small cell lung cancer (NSCLC), the clinical significance of ROS1 de novo mutation has not yet been understood. We sought to elucidate the predictive effect of ROS1 mutation for immune checkpoint inhibitor (ICI) therapy in melanoma.MethodsThe Cancer Genome Atlas [TCGA (n = 10967)] and Memorial Sloan Kettering Cancer Center [MSK (n = 10,945)] datasets, as well as two clinical cohorts of melanoma received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…Recently, entrectinib and crizotinib, both RTK inhibitors, have been approved for treating ROS1‐positive solid tumors 7 . In cutaneous melanoma, de novo mutations in ROS1 has been shown to result in improved OS for patients treated with immunotherapy, along with having a higher TMB 8 . We also observed in our cohort that ROS1‐mutated cases had a higher TMB, likely contributing to their improved OS.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Recently, entrectinib and crizotinib, both RTK inhibitors, have been approved for treating ROS1‐positive solid tumors 7 . In cutaneous melanoma, de novo mutations in ROS1 has been shown to result in improved OS for patients treated with immunotherapy, along with having a higher TMB 8 . We also observed in our cohort that ROS1‐mutated cases had a higher TMB, likely contributing to their improved OS.…”
Section: Discussionsupporting
confidence: 66%
“…7 In cutaneous melanoma, de novo mutations in ROS1 has been shown to result in improved OS for patients treated with immunotherapy, along with having a higher TMB. 8 We also observed in our cohort that ROS1-mutated cases had a higher TMB, likely contributing to their improved OS. Furthermore, one case report describes complete response to crizotinib therapy in a HNMM patient harboring a ROS1 mutation.…”
Section: Discussionsupporting
confidence: 64%
“…For example, Johnson et al demonstrated that melanoma patients with NRAS mutations had a higher response rate to first-line ICIs treatment with ipilimumab or anti-PD-L1 antibody than those with wild type [ 14 ]. It was also noted that melanoma patients with ROS1 mutations yielded longer OS from ICIs [ 15 ]. These results suggest that certain genetic mutations may be reliable predictive markers of ICIs efficacy in melanoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, evidences from both in vivo and in vitro studies revealed ROS1 could regulate the expression of PD-L1 and participate in immune escape through the activation of ROS1-SHP2 - and MEK-ERK -signaling pathways in lung cancer [ 2 ]. In melanoma, ROS1 mutation was associated with an enrichment of DNA-damage-response-related processes and DNA-repair-related molecules [ 3 ], which might lead to the enhanced immune surveillance. Here, we conducted a comprehensive bioinformatic and clinical analysis to study the characteristics of ROS1 mutation and its association with pan-cancer immunotherapy (Suppl.…”
mentioning
confidence: 99%